The Effectiveness of the Short Story Writing Program in Developing Students' Creative Writing Skills - Sirojul Munir; Hendaryan (Jurnal Pendidikan Indonesia, 2023)
This research is motivated by the low ability of creative writing. Students still find it difficult to write literary works, especially short stories. This study aims to analyze the effect of the short story writing program on the creative writing skills of high school students. Analysis was carried out on aspects of word choice (shape, synonyms, collocation) and aspects of creativity in making short stories (fluency, flexibility, originality and elaboration). The method used in this research is quasi-experimental. The instrument used is a test of creative writing skills and indicators for assessing aspects of word choice and creativity. Research participants consisted of 250 high school students. The number of samples was divided into 125 students in the experimental group and 125 students in the control group. Data were analyze using descriptive statistics, t test, analysis of variance test (ANOVA) to investigate significant differences between the means and calculate the effect size using SPSS. The results of the study show that short story writing programs can improve students' creative writing skills. The improvement of students' short story writing skills can be seen in the improvement in the quality of writing from several aspects, namely the aspect of word choice (forms, synonyms, collocations) and aspects of creativity in making short stories (fluency, flexibility, originality and elaboration). From the results of the study it can be concluded that this creative writing program can improve the ability to write short stories.